Pathophysiological significance of Stim1 mutation in sympathetic response to stress and cardiovascular phenotypes in SHRSP/Izm: In vivo evaluation by creation of a novel gene knock-in rat using CRISPR/Cas9 - Batbayar Odongoo; Hiroki Ohara; Davis Ngarashi; Takehito Kaneko; Yayoi Kunihiro; Tomoji Mashimo; Toru Nabika (Clinical and Experimental Hypertension, 2021)
Genetic approach using rat congenic lines between SHRSP/Izm and WKY/Izm identified stromal interaction molecule 1 (Stim1), an essential component of store-operated Ca2+ entry (SOCE), as a promising candidate gene responsible for the exaggerated sympathetic response to stress in SHRSP. Since SHRSP has a nonsense mutation in Stim1 resulting in the expression of a truncated form of STIM1 that caused reduction of SOCE activity in primary cultured cerebral astrocytes, we created SHRSP/Izm knocked-in with the wild-type Stim1 (KI SHRSP) by the CRISPR/Cas9 method to investigate whether the functional recovery of STIM1 would mitigate sympatho-excitation to stress in vivo in SHRSP. No potential off-target nucleotide substitutions/deletions/insertions were found in KI SHRSP. Western blotting and fluorescent Ca2+ imaging of astrocytes confirmed wild-type STIM1 expression and restored SOCE activity in astrocytes from KI SHRSP, respectively. Blood pressure (BP) measured by the tail-cuff method at 12, 16, and 20 weeks of age did not significantly differ between SHRSP and KI SHRSP, while the heart rate of KI SHRSP at 16 and 20 weeks of age was significantly lower than that of age-matched SHRSP. Unexpectedly, the sympathetic response to stress (evaluated with urinary excretion of norepinephrine under cold stress and BP elevation under cold/restraint stress) did not significantly differ between SHRSP and KI SHRSP. The present results indicated that the functional deficit of STIM1 was not a genetic determinant of the exaggerated sympathetic response to stress in SHRSP and that it would be necessary to explore other candidates within the congenic fragment on chromosome 1.